Mining Data Analysis Using CRISP-DM to Implement Successfully Multipurpose Financing at Astra Credit Companies (ACC) Branch Bogor - Erwin Husein, Emil. R. Kaburuan, Mauritsius Tuga (International Journal of Advanced Science and Technology, 2020)
The growing need for life to encourage the emergence of a finance company. This is due to financing has become one of the solutions to help meet the needs of a person's life. Astra Credit Companies (ACC) is a finance company that provides financing in the form of a multipurpose loan. To optimize financing made by the company, required an analysis of customer segmentation. It is intended to allow better targeted financing deals. The focus in this study is used to finance the purchase of secondhand vehicles types. The analysis was conducted by classifying customers based on job data, vehicle type, the installment, the tenor, credit quality and payment. The technique used is the technique of applying clustering with K-means clustering algorithm. The method used is the CRISP-DM. Results from this study is the formation of three groups where each group has its own characteristics. To make offers multipurpose financing through guarantees manifold motor vehicle reg car, the company can offer to potential customers who already do segmentation so easy to do marketing.